Modus Operandi of a Serial Sex Offender - Spytska, Liana (NBP. Nauka, bezbednosti, policija, 2024)
The purpose of the study was to investigate the modus operandi of serial sex offenders. The main method of research was criminal profiling based on 50 cases in the Unified State Register of Court Decisions, for which the verdict was passed. A number of indicators were investigated, including the characteristic method of attack, the choice of the victim, the establishment of contact with the victim, and the method of committing the offence. As a result, it was established that criminals can be divided into two characteristic types according to modus operandi: the first type carries out a sudden attack or pursuit of the victim, is characterised by a violent method of attack, and the crime is often accompanied by bodily harm. The psycho-emotional portrait of attackers of this type is characterised by greater impulsivity and spontaneity of actions. The main motivation for committing a crime is to satisfy a sexual urge. Criminals of the second cluster tend to commit planned attacks, mostly indoors, establish contact with the victim, resort to manipulation and threats. They have a less pronounced passion and tend to plan crimes. The dominant motivation can be either sexual or the satisfaction of sadistic tendencies and dominance. This study focuses on the characteristic modus operandi and psychological characteristics of criminals who commit serial sexual offences. The results may be useful for specialists in the field of criminal law, criminology, forensic science, and forensic psychology.